PARASITÓIDES E HIPERPARASITÓIDES DE MÚMIAS DE Brevicoryne brassicae (Linnaeus, 1758) (HEMIPTERA – HOMOPTERA: APHIDIIDAE) - Souza, Bernardete Maria de; Bueno, Vanda Helena Paes (REVISTA DE AGRICULTURA, 2015)
PARASITÓIDES E HIPERPARASITÓIDES DE MÚMIAS DE Brevicoryne brassicae (Linnaeus, 1758) (HEMIPTERA – HOMOPTERA: APHIDIIDAE)